Problematical Nature of Experience and Processuality of Law: Interpretation and Outcomes of the Aristotelian Conception of Becoming - Moro, Paolo (Acta Philosophica, 2025)
The essay explores the relationship between the problematic nature of experience and the processuality of law, analyzing the Aristotelian conception of becoming in the light of Enrico Berti’s thought, according to which the authentic problem of philosophy is the question of the multiplicity of experience. After examining the question of being in becoming, the author highlights that for Aristotle change is an undeniable and original dimension of existence (1-3) and deepens the theme of the problematic and procedural nature of reality, in which the social practice of law assumes a primary role (4). Particular attention is paid to the link between becoming and controversy in order to demonstrate that the instability of experience generates conflicts that require the intervention of law through the trial, as an organized response to the management of change and litigation (5-6). The conclusion reflects critically on the complexity of the judicial process, highlighting the theoretical and practical challenges posed by its dialectic nature (7).